2007
DOI: 10.5089/9781451866650.001
|View full text |Cite
|
Sign up to set email alerts
|

Interest Rate Spreads in English-Speaking African Countries

Abstract: This Working Paper should not be reported as representing the views of the IMF.The views expressed in this Working Paper are those of the author(s) and do not necessarily represent those of the IMF or IMF policy. Working Papers describe research in progress by the author(s) and are published to elicit comments and to further debate. This paper examines interest rate spreads in English-speaking African countries. Higher spreads were found to be associated with lower inflation, a greater number of banks, and gre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
37
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(40 citation statements)
references
References 19 publications
3
37
0
Order By: Relevance
“…This has increased competition among financial institutions, and introduced strong business practices, and risk 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 J o u r n a l o f E c o n o m i c a n d M a n a g e m e n t S t u management systems which may be creating higher spreads (Bank of Ghana, 2007;Adu, et al, 2013;Ackah and Asiamah, 2014). Crowley (2007), Ben Naceur and Goaied (2008), and Garr and Kyereboah-Coleman (2013) provide similar results for sub-Saharan African countries, Tunisia and Ghana respectively.…”
Section: Insert Table 4 Herementioning
confidence: 65%
See 1 more Smart Citation
“…This has increased competition among financial institutions, and introduced strong business practices, and risk 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 J o u r n a l o f E c o n o m i c a n d M a n a g e m e n t S t u management systems which may be creating higher spreads (Bank of Ghana, 2007;Adu, et al, 2013;Ackah and Asiamah, 2014). Crowley (2007), Ben Naceur and Goaied (2008), and Garr and Kyereboah-Coleman (2013) provide similar results for sub-Saharan African countries, Tunisia and Ghana respectively.…”
Section: Insert Table 4 Herementioning
confidence: 65%
“…These arguments notwithstanding, spreads have also been found to be influenced by macroeconomic factors (see Randall, 1998;Franken, 2002, 2003;Tennant, 2006;Crowley, 2007;Folawewo, and Tennant, 2008;Sheriff and Amoako, 2014 Bawumia, et al, 2005;Aboagye et al, 2008;Kwakye, 2010;Garr and Coleman, 2013;Sarpong et al, 2013;Churchill et al, 2014;Sheriff and Amoako, 2014;AmuakwahMensah and Marbuah, 2015) the present paper differ from these ones for the following reasons. First, it introduces money growth and a measure of institutional quality in determining interest rate spread.…”
Section: Source: Authorsmentioning
confidence: 99%
“…A study by Afanasieff, Lhacer and Nakane (2002) suggest that macroeconomic variables are the most relevant factors explaining the behavior of bank interest rate spreads in Brazil. Crowley (2007) found that higher spreads are associated with lower inflation. Similarly, a study by Brock and Suarez (2000) shows that beyond bank specific variables, uncertainty in the macroeconomic environment facing banks appears to increase interest spreads.…”
Section: Wwwccsenetorg/ibrmentioning
confidence: 99%
“…However amendments to the Finance Bill 2014 were passed in August 2014 exempting it from having to pay VAT on aircraft and spare part imports. Interest rate is the price a borrower pays for the use of money they borrow from a lender or fee paid on borrowed assets (Crowley, 2007). KQ's exposure to market risk due to changes in interest rates primarily relates to its cash deposits and borrowings.…”
Section: Independent Variable Dependent Variable Figure 1: Conceptualmentioning
confidence: 99%